Susceptibility of Tribolium castaneum life stages exposed to elevated temperatures during heat treatments of a pilot flour mill: influence of sanitation, temperatures attained among mills floors, and costs - Brijwani, Monika; Subramanyam, Bhadriraju; Flinn, Paul W.; Langemeier, Michael R.; Hartzer, Michelle; Hulasare, Rajshekhar (My University, 2012)
The influence of sanitation on responses of life stages of the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), was investigated in a pilot flour mill subjected to three, 24-h heat treatments by using forced-air gas heaters fueled by propane. Two sanitation levels, dusting of wheat flour and 2-cm-deep flour, were created in 25 plastic bioassay boxes, each holding eggs, young larvae, old larvae, pupae, and adults of T. castaneum plus two temperature sensors. Data loggers (48) were placed on the five mill floors to record air temperatures. The time required to reach 50°C, time above 50°C, and the maximum temperature among mill floors and in bioassay boxes were measured. The maximum temperature in bioassay boxes and in the mill was lower on the first floor than on other floors. This trend was apparent in time required to reach 50°C and time above 50°C, especially in compartments with 2-cm-deep flour. The mean ± SE mortality of T. castaneum life stages on the first floor was 55.5 ± 12.9–98.6 ± 0.8%; it was 93.2 ± 6.7–100 ± 0.0% on other floors. Adults were the least susceptible stage. Mortality of T. castaneum stages in compartments with 2-cm-deep flour was generally lower than those with flour dust. Costs for the three heat treatments ranged from US$27,438 to $28,838. An effective heat treatment can be conducted within 24 h, provided temperatures on mill floors reach 50°C in 8–12 h and are held above 50°C for at least 10–14 h, with maximum temperatures held between 50 and 60°C.
Keywords: Heat treatment; Temperature; Sanitation; Insect mortality; Economics; Tribolium castaneum